Epidemiological characteristics of Vibrio parahaemolyticus outbreaks, Zhejiang, China, 2010–2022 - Chen, Lili; Wang, Jikai; Chen, Jiang; Zhang, Ronghua; Zhang, Hexiang; Qi, Xiaojuan; He, Yue (Frontiers in Microbiology, 2023)
Background: Vibrio parahaemolyticus is the most common foodborne pathogen and causes a significant disease burden. We aim to understand the epidemiological characteristics of foodborne disease outbreaks caused by Vibrio parahaemolyticus in Zhejiang Province, and to provide ideas for the targeted prevention and control of foodborne diseases. Methods: Descriptive statistical methods were used to analyze the data of outbreaks caused by Background: Vibrio parahaemolyticus is one of the most common foodborne pathogen and causes a significant disease burden. We aim to understand the epidemiological characteristics of foodborne disease outbreaks caused by Vibrio parahaemolyticus in Zhejiang Province, and to provide ideas for the targeted prevention and control of foodborne diseases. Methods: Descriptive statistical methods were used to analyze the data of outbreaks caused by Vibrio parahaemolyticus reported by centers for disease control (CDCs) at different levels in Zhejiang Province through Foodborne Disease Outbreaks Surveillance System (FDOSS) during 2010-2022. Results: From 2010 to 2022, a total of 383 outbreaks caused by Vibrio parahaemolyticus were reported by 90 CDCs in 11 regions of Zhejiang Province, resulting in 4,382 illnesses, 326 hospitalizations and 1 death. The number of outbreaks from July to September accounted for 77.54% of all outbreaks (297 outbreaks, 297/383). The number of restaurant-associated outbreaks was the largest, accounting for 57.96% of the total outbreaks, followed by those related to staff canteens (15.40%) and rural banquets (11.23%). The food vehicles of most outbreaks were aquatic products (31.85%). Ready-to-eat foods (including Chinese cold dish and cooked meat products) accounted for 12.53% of outbreaks. Serotype O3K6 (81.94%,118/144) was the main serotype leading to outbreaks from 2010 to 2020, while serotype O10K4(57.89%,33/57) was the main serotype from 2021 to 2022. Conclusions: An in-depth and comprehensive analysis of the data of long-term surveillance of outbreaks caused by Vibrio parahaemolyticus can understand the characteristics of outbreaks caused by this pathogen, analyze long-term regularity and latest trends, and determine the direction of priority intervention, which is conducive to guiding targeted policies to reduce outbreaks.